Population pharmacokinetics and pharmacogenetics of alcohol in Chinese and Indians in Singapore. (12th December 2012) - Seng, K. Y.; Limenta, L. M. G.; Heng, D.; Lee, E. J. D.
Summary What is known and Objective: Interindividual variability in alcohol pharmacokinetics is influenced by a number of factors, including polymorphisms in genes mediating alcohol pharmacology, ethnicity, sex and body size. Several studies have evaluated the population pharmacokinetics of alcohol from breath alcohol measures. None of these studies, however, have evaluated ethnicity and alcohol‐metabolizing enzyme genotypes as covariates in their population pharmacokinetic modelling. We aimed to develop a population pharmacokinetic model using clinical and genetic factors and to identify covariates that influenced interindividual variability in alcohol clearance and volume of distribution. Methods: Hundred and eighty healthy subjects (90 Chinese and 90 Indians; 45 males and 45 females from each ethnic group) ingested a vodka–orange juice mixture to simulate social drinking. Subjects were genotyped for the ADH1B (Arg48His), ALDH2 (Glu504Lys) and CYP2E1 (c.‐1293G>C and c.‐1053C>T) polymorphisms. A base pharmacokinetic model was developed using the nonmem software (NONMEM Project Group, University of California, San Francisco, San Francisco, CA, USA) to determine the alcohol clearance and volume of distribution. The model was extended to include covariates that influenced the between‐subject variability. Results and Discussion: Body weight and sex significantly influenced absorption rate and volume of distribution of alcohol. Body weight and ADH1B Arg48His polymorphism significantly influenced alcohol clearance. The Michaelis–Menten elimination rate (Vmax) was decreased by 10% in homozygous ADH1B*1/*1 subjects. Ethnicity was not determined to be a significant covariate in the final population pharmacokinetic model. What is new and Conclusion: Gender and body weight were covariates that contributed most to explaining the observed interindividual alcohol pharmacokinetic variability. Of the four SNPs examined in this study, only ADH1B Arg48His polymorphism had a significant, though modest, effect on the pharmacokinetics of alcohol.